Causal effects of hypertension on risk of erectile dysfunction: A two-sample Mendelian randomization study - Wang, Zheng; Wang, Yunyun; Xiong, Jiachao; Gan, Xinxin; Bao, Yewei; Jiang, Aimin; Zhou, Ye; Huangfu, Zhao; Yang, Yiren; Liu, Zhiyong; Xia, Demeng; Wang, Linhui (Frontiers in Cardiovascular Medicine, 2023)
Background: Erection dysfunction has been associated with hypertension in several epidemiological and observational studies. But the causal association between hypertension and erectile dysfunction requires further investigation. Methods: A two-sample Mendelian Randomization was conducted to analyze the causal effect of hypertension on risk of erection dysfunction. Large-scale publicly available Genome Wide Association Study data was applied to estimate the putative causality between hypertension and risk of erectile dysfunction. 67 independent single nucleotide polymorphisms were selected as instrumental variables. Inverse-variant weighted, maximum likelihood, weighted median, penalized weighted median and MR-PRESSO approaches were utilized in MR analyses. Heterogeneity test, horizontal pleiotropy test and leave-one-out method were used to prove the stability of the results. Results: Totally, all P values were less than 0.05, demonstrating positive causal link between hypertension and risk of erectile dysfunction in multiple MR methods, such as inverse-variant weighted (random and fixed effect) (OR 3.8315, 95% CI 2.3004-6.3817, P=0.0085), maximum likelihood (OR 3.8877, 95% CI 2.3224-6.5081, P=0.0085), weighted median (OR 4.9720, 95% CI 2.3645-10.4550, P=0.0309), penalized weighted median (OR 4.9760, 95% CI 2.3201-10.6721, P=0.0355) and MR-PRESSO (OR 3.6185, 95% CI 2.2387-5.8488, P=0.0092). Sensitivity analysis detected no evidence of heterogeneity, pleiotropy or outlier single nucleotide polymorphisms. Conclusion: The study revealed a positive causal link between the presence of hypertension and risk of erectile dysfunction. More attention should be paid during the management of hypertension with the purpose of preventing erectile dysfunction or improving erectile function.